Uji Kekerabatan Aksesi Cengkeh di Kebun Percobaan Sukapura - Cici Tresniawati; Enny Randriani (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2011)
Clove (Syzygium aromaticum L. Merril & Perry) is One of the Oldest Spices in the World. Clove is an evergreen tree with unopened flower bud. It is indigenous to Moluccas Island of Indonesia. Clove are mainly used as an ingredient of a variety of food specialties, beverages, medicines, and cigarettes industry. It is important to have germplasm collection in plant breeding program. Twenty eight accessions have been planted at Sukapura Experimental Garden, Probolinggo, East Java. The objective of this study was to estimate the genetic relationship among 28 clove accessions. The observations were made on fifteen morphological characters and six yield component characters. Eleven morphological characters and one yield component character had wide genetic variability. By applying cluster analysis, a dendogram was constructed to differentiate morphological differences among the accessions. The dendogram showed that the grouping of the accessions at different hierarchical levels, based upon the variation was observed. Results showed that the accession of clove could be classified into four groups. The first group only consisted of Zanzibar 5, the second group consisted of Zanzibar 13 and Siputih 5, the third group only consisted of Zanzibar 8, and 24 accessions belong to the fourth groups. AbstrakCengkeh (Syzygium aromaticum L. Merril & Perry) merupakan tanaman rempah tertua di dunia yang berasal dari kepulauan Maluku. Bunga kering cengkeh sering digunakan sebagai bahan untuk bumbu, obat-obatan, kosmetik, dan industri rokok. Koleksi plasma nutfah merupakan hal yang penting dalam suatu program pemuliaan tanaman. Dua puluh delapan aksesi cengkeh ditanam di Kebun Percobaan Sukapura, Probolinggo, Jawa Timur. Penelitian ini bertujuan mengetahui hubungan kekerabatan di antara 28 aksesi cengkeh. Pengamatan dilakukan terhadap 15 karakter morfologi dan 6 karakter komponen hasil. Sebelas karakter morfologi dan satu karakter komponen hasil memiliki keragaman genetik yang luas. Dengan menggunakan analisis kluster ditentukan pengelompokan berdasarkan perbedaan sifat morfologi di antara 28 aksesi tanaman cengkeh. Gerombol I, yaitu Zanzibar 5, Gerombol II terdiri atas Zanzibar 13 dan Siputih 5, Gerombol III, yaitu Zanzibar 8, dan Gerombol IV terdiri atas 24 aksesi lainnya.